DE LA GÂNDIREA CREATIVĂ SPRE O BIBLIOTECĂ INOVATIVĂ - ANDREEV, director, Filiala „A. Mickiewicz”, Oxana (BIBLIOPOLIS, 2020)
The article is about the ideas generated and implemented in Polish library and causes that were provoked librarians to innovate new ways of library services and products. The author demonstrates the effectiveness of new methods that benefits the library.